Adaptive Motion Control Middleware for Teleoperation Based on Pose Tracking and Trajectory Planning - Blank, Andreas; Karlidag, Engin; Zikeli, Georg; Metzner, Maximilian; Franke, Jörg (Annals of Scientific Society for Assembly, Handling and Industrial Robotics 2021, 2021)
Concurrent with autonomous robots, teleoperation gains importance in industrial applications. This includes human-robot cooperation during complex or harmful operations and remote intervention. A key role in teleoperation is the ability to translate operator inputs to robot movements. Therefore, providing different motion control types is a decisive aspect due to the variety of tasks to be expected. For a wide range of use-cases, a high degree of interoperability to a variety of robot systems is required. In addition, the control input should support up-to-date Human Machine Interfaces. To address the existing challenges, we present a middleware for teleoperation of industrial robots, which is adaptive regarding motion control types. Thereby the middleware relies on an open-source, robot meta-operating system and a standardized communication. Evaluation is performed within defined tasks utilizing different articulated robots, whereby performance and determinacy are quantified. An implementation sample of the method is available on: https://github.com/FAU-FAPS/adaptive_motion_control.<br
Keywords: Industrial Robots; Teleoperation; Motion Control

High-precision assembly of electronic devices with lightweight robots through sensor-guided insertion - Metzner, Maximilian; Leurer, Sebastian; Handwerker, Andreas; Karlidag, Engin; Blank, Andreas; Hefner, Florian; Franke, Jörg (Procedia CIRP, 2020)
Through-hole devices still play an important role in power electronics production. Due to a high number of variants in this field, an automated placement by special machines is often not economically feasible. The resulting manual process is characterized by monotony, ergonomic strain and high labor cost. As a result, a partial automation, using lightweight robots in hybrid assembly system, yields high potential. The lower stiffness and resulting accuracy deficiency of lightweight robots compared to common industrial robots, combined with the precision requirements and inherent fragility of the devices, prohibits the deployment of such systems. In this contribution, a scalable setup and strategies for visual and force-torque guided tactile insertion of such devices is presented and evaluated. A library, based on a system for the offline-programming of such tasks, is used to decrease implementation efforts. A performance evaluation of the system on printed circuit boards with multiple different devices is conducted.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Electronics production; Lightweight robots; Offline programming; Peg in Hole

Hybrid Environment Reconstruction Improving User Experience and Workload in Augmented Virtuality Teleoperation - Blank, Andreas; Kosar, Emir; Karlidag, Engin; Guo, Qiang; Kohn, Sebastian; Sommer, Oliver; Walter, Jonas; Herbert, Meike; Seßner, Julian; Querfurth, Frank; Metzner, Maximilian; Franke, Jörg (Procedia Manufacturing, 2021)
Concurrent with autonomous robots, teleoperation gains importance in industrial applications. This includes remote intervention scenarios and human-robot-cooperation during complex or harmful tasks operated from a distance. For an efficient teleoperation, an interface achieving a good user experience and relieving workload of the operators is decisive. Whereas virtual reality allows a spatial integration, environment reconstruction is often based on point clouds in combination with pre-known object models. Challenges exist in spatial representation, through bandwidth limitations and sensor interferences. Furthermore, the potential of knowledge augmentation for workload improvement is often not fully utilized. To overcome these challenges, we present a hybrid environment reconstruction method, which is adaptive regarding the integration of different data sources as well as their derived semantic information levels. For evaluation, a user study is performed. Thereby known procedures to measure usability, immersion, user experience and operator workload serve for evaluation and comparison.<br
Keywords: Teleoperation; Virtual Reality; Environment Reconstruction; Knowledge Augmentation; Human-in-the-Loop

Virtual Commissioning of 6 DoF Pose Estimation and Robotic Bin Picking Systems for Industrial Parts - Metzner, Maximilian; Weissert, Soeren; Karlidag, Engin; Albrecht, Felix; Blank, Andreas; Mayr, Andreas; Franke, Jörg (IFAC-PapersOnLine, 2019)